Diagnosis, evolution and treatment of hypothalamic-pituitary clinically non functioning tumors - Garmendia-Lorena, Fausto (2024)
Objective: To describe the characteristics of clinically non-functioning hypothalamic-pituitary tumors (THCNF). Material and methods: Descriptive, cross-sectional, retrospective study of 67 THCNF stories. from patients who attended the author's private practice, collected from January 2 to March 31, 2023 with manifestations of expansion of the hypothalamus-pituitary region. Information is given on age, weight, height, BMI, blood pressure, concentrations of prolactin (PRL), thyrotrophic hormone (TSH), luteotrophic hormone (LH), follicle-stimulating hormone (FSH), somatotropin (STH), thyroxine (T4), triiodo-thyronine (T3), cortisol (F), testosterone (T) in men, estradiol (E2) in women, glucose (G). Stimulatory tests with TRH, GnRH, insulin hypoglycemia, x-rays, ocular campimetry and treatment. Results: 53.7% women, 42.2± 15.5 years old, weight 71.1kg, height 1.63m, BMI 26.1, BP 130/75 mmHg, PRL14.9±12.3 ng/ml, STH 1.00 ±1.51 ng/ml, TSH 4.06±3.65 mIU/L, LH 5.69±5.28 IU/L, T4 6.86±2.68 ug/dl, T3 92.0±20.8 ng/dl, F 10.4 ±7.52 ug/dl, T 2.68±3.25 ng/dL, E2 28.3±9.07 pg/ml. TRH test: 6.56-14.8-14.8 mIU/L TSH. GnRH test: 4.0, 6.09, 6.11, 8.32, 6.87 IU/L LH. Insulin hypoglycemia: 0.95, 0.94, 2.24, 1.23, 1.4 ng/ml STH; 6.82, 9.64, 12.3, 11.6, 9.9 ug/dL cortisol. Blood glucose 86.6±7.08, 39.5±11.0, 63.3±10.9, 74.0±12.7, 77.0±12.0. All showed an increase in the sella turcica. Except for 3 who had normal vision, the rest presented altered vision from bitemporal hemianopia to blindness. The majority underwent transsphenoidal hypophysectomy, some received additional radiotherapy. Conclusions: THCNF had normal basal hormonal concentrations and limited responses to stimulatory tests.